2018
DOI: 10.37773/ees.v1i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Reading History and Power in Urban Landscapes: The Lens of Urban Political Ecology

Abstract: This essay sketches some of these features and their implications, employing five intersecting rubrics—hybrids, boundaries, histories, values, and peripheries. Together, these frames build an account of how the urban engine (or metabolism, in the language of urban political ecology), with its distinctive pace and drivers, assembles dynamic entities that defy easy categorization and carry powerful political stakes. The essay draws on a selection of empirical work across Indian cities (including my own writings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…While we were unable to uncover specific details about the use of the pond before the creation of the park, oral histories conducted with long-term residents of the neighborhood indicated that the pond had become a dumping site for garbage, and establishment of the park was advocated as a way to address this problem. Additionally, at the time of the development of this green space, various state and parastatal bodies in the city of Chennai were actively involved in a campaign to eliminate centuries-old engineered tanks and seasonal lakes known as eris through infilling as a means of enhancing the supply of housing, infrastructure, and institutions (Coelho 2018). These factors point to a tension where one type of commons was sacrificed to create other types of social infrastructure.…”
Section: Methods and Research Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…While we were unable to uncover specific details about the use of the pond before the creation of the park, oral histories conducted with long-term residents of the neighborhood indicated that the pond had become a dumping site for garbage, and establishment of the park was advocated as a way to address this problem. Additionally, at the time of the development of this green space, various state and parastatal bodies in the city of Chennai were actively involved in a campaign to eliminate centuries-old engineered tanks and seasonal lakes known as eris through infilling as a means of enhancing the supply of housing, infrastructure, and institutions (Coelho 2018). These factors point to a tension where one type of commons was sacrificed to create other types of social infrastructure.…”
Section: Methods and Research Settingmentioning
confidence: 99%
“…The acquisition of land purportedly for green spaces is also sometimes combined with commercial development. This suggests that the creation of public spaces can be used as an excuse to open up lands occupied by the poor to real-estate development, as observed in the case of the Citi Center Mall in Chennai (Coelho 2018). Promoting inclusive and accessible parks as an alternative to the hegemony of shopping malls and without population displacement becomes all the more relevant in this context.…”
Section: Linking Need Satisfaction To the Politics Of Urban Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…The urbanization of nature is a process of boundary‐inscription that makes land from water, parks from forests, flatlands from hills. As some scholars argue (Mathur and Da Cunha, 2008; Bhattacharya, 2018; Coelho, 2018), the land‐water boundary in lakes, rivers or flood plains is more a smudgy, shifting, seasonal zone than a line. But the urban eye on nature is focused on specific interests and sees in categorical metrics.…”
Section: Waterlines: Boundaries Flows and Infrastructuresmentioning
confidence: 99%
“…A growing body of writing in the urban political ecology (UPE) tradition has shown how urban systems—rivers, beaches, municipal water and transport—can be analysed as socio-natural assemblages of human, more-than-human, technological and natural processes (Coelho, 2018; Heynen, 2014; Swyngedouw & Heynen, 2004). But eris are especially hybrid given their engineered origins and their subsequent embedding in matrices of contested social uses.…”
Section: Introduction: the Urban Tank As A Boundary Objectmentioning
confidence: 99%